2007
DOI: 10.1088/0268-1242/22/9/017
|View full text |Cite
|
Sign up to set email alerts
|

Wire-like characteristics in stacked InAs/GaAs quantum dot superlattices for optoelectronic devices

Abstract: The wire-like characteristics of stacked InAs/GaAs quantum dot (QDs) superlattices induced by the vertically electronic coupling effect were demonstrated by surface photovoltaic and photoluminescence measurements. It was found that the surface photovoltaic signal can be enhanced by up to more than 100 times due to the wire-like behavior along the growth direction. We also found that the emission from the cleaved edge surface is strongly anisotropic, which suggests a possibility of fine tuning the polarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The effect of vertical coupling of the bandgap of the active region is studied in [14] where it has been shown that the surface photovoltaic signal can be enhanced by up to more than 100 times due to vertical coupling. To the best of our knowledge there is no work in the literature that studies the vertical coupling effects between multiple stacks of QD layers in a semiconductor optical amplifier.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of vertical coupling of the bandgap of the active region is studied in [14] where it has been shown that the surface photovoltaic signal can be enhanced by up to more than 100 times due to vertical coupling. To the best of our knowledge there is no work in the literature that studies the vertical coupling effects between multiple stacks of QD layers in a semiconductor optical amplifier.…”
Section: Introductionmentioning
confidence: 99%